2012
DOI: 10.36076/ppj.2012/15/297
|View full text |Cite
|
Sign up to set email alerts
|

Removal of a Vertebral Metastatic Tumor Compressing the Spinal Nerve Roots via a Single-Port, Transforaminal, Endoscopic Approach Under Monitored Anesthesia Care

Abstract: Spinal cord or nerve root compression from an epidural metastasis occurs in 5-10% of patients with cancer and in up to 40% of patients with preexisting nonspinal bone metastases. Most metastatic spine diseases arise from the vertebral column, with the posterior half of the vertebral body being the most common initial focus, and/or the paravertebral region, tracking along the spinal nerves to enter the spinal column via the intervertebral foramina. An 82-year-old man diagnosed with sigmoid colon cancer and live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…The full-endoscopic techniques have been reported since 2012 3 . Their use was aimed at treating neuropathic pain by decompression of nervous structures compressed by an expansive metastatic lesion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The full-endoscopic techniques have been reported since 2012 3 . Their use was aimed at treating neuropathic pain by decompression of nervous structures compressed by an expansive metastatic lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Their use was aimed at treating neuropathic pain by decompression of nervous structures compressed by an expansive metastatic lesion. Biopsy and decompression of metastatic lesions of the spine were performed by transforaminal endoscopic access 3,7,19 . In 2015, a study demonstrated the possibility of complete resection of a lesion in the lumbar spine for the first time 16 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the development of spinal endoscopic techniques in recent years, the indications have expanded from degenerative spinal diseases to spinal infections and even spinal neoplastic diseases [12][13][14]. Depending on the number and size of working channels, spinal endoscopy can be divided into several different systems, including microendoscopic and percutaneous endoscopic surgery.…”
Section: Discussionmentioning
confidence: 99%